2024
DOI: 10.1002/cbdv.202400385
|View full text |Cite
|
Sign up to set email alerts
|

Lachnuoic Acids A−F: Ambuic Acid Congeners from a Saprotrophic Lachnum Species

Kunthida Phutthacharoen,
Rita Toshe,
Syeda J. Khalid
et al.

Abstract: Chemical prospection of an extract derived from a saprotrophic fungus Lachnum sp. IW157 resulted in the isolation and characterization of six unprecedentedly reported ambuic acid analogues named lachnuoic acids A–F (1–6). Chemical structures of 1–6 were determined based on comprehensive 1D and 2D NMR spectroscopic analyses together with HR‐ESI‐MS spectrometry. The relative configurations of 1–3 were defined by ROESY spectroscopic analyses while their absolute configurations were unambiguously determined by Mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…According to our main research aim to find out new anti-infective and/or biocontrol agents, all isolated compounds were subjected to cytotoxic, antimicrobial, antiviral, and nematicidal activity assays following the previously reported protocols. ,,, However, the obtained results (Tables S6–S8) revealed that none of the tested compounds revealed activity in any of the conducted assays. Despite that, these negative results encouraged us to exploit the reported literature discussing oligopeptides for finding related derivatives with potential bioactivities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to our main research aim to find out new anti-infective and/or biocontrol agents, all isolated compounds were subjected to cytotoxic, antimicrobial, antiviral, and nematicidal activity assays following the previously reported protocols. ,,, However, the obtained results (Tables S6–S8) revealed that none of the tested compounds revealed activity in any of the conducted assays. Despite that, these negative results encouraged us to exploit the reported literature discussing oligopeptides for finding related derivatives with potential bioactivities.…”
Section: Resultsmentioning
confidence: 99%
“…baumannii), Chromobacterium violaceum, Escherichia coli, and Pseudomonas aeruginosa (P. aeruginosa)), and five fungal species (Candida albicans, Mucor hiemalis, Rhodotorula glutinis, Schizosaccharomyces pombe, and Wickerhamomyces anomalus), utilizing established methodologies. ,,, Methanol served as the negative control with a volume of 20 μL, while the choice of positive controls was tailored to the specific organism under investigation. For bacterial strains, oxytetracycline, ciprofloxacin, kanamycin, and gentamicin were employed as references for B.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecules 2024, 29, x FOR PEER REVIEW A literature search of 1 revealed its common structural features of strobiloscyphones [10], pestallic acids [11], dentipellin [4], and the recently reported lachnoic acids [12], where they shared the presence of a 2-cyclohexenone moiety in their structures. A careful interpretation of the obtained 1D and 2D NMR spectral data of 1 (Table 1, Figure 2) suggested the structure depicted in Figure 1, with a 1,1-dimethyl-2-propenyl functionality being attached at C-6.…”
Section: Resultsmentioning
confidence: 99%